Advanced Computer and Communication Engineering Technology : Proceedings of the 1st International Conference on Communication and Computer Engineering - Sulaiman, Hamzah Asyrani; Othman, Mohd Azlishah; Othman, Mohd Fairuz Iskandar; Rahim, Yahaya Abd; Pee, Naim Che (Lecture Notes in Electrical Engineering,, 2015)
This book covers diverse aspects of advanced computer and communication engineering, focusing specifically on industrial and manufacturing theory and applications of electronics, communications, computing, and information technology. Experts in research, industry, and academia present the latest developments in technology, describe applications involving cutting-edge communication and computer systems, and explore likely future directions. In addition, access is offered to numerous new algorithms that assist in solving computer and communication engineering problems. The book is based on presentations delivered at ICOCOE 2014, the 1st International Conference on Communication and Computer Engineering. It will appeal to a wide range of professionals in the field, including telecommunication engineers, computer engineers and scientists, researchers, academics, and students.